Hubungan Daerah Tempat Tinggal dengan Kejadian Dermatitis Atopik - Izdihar, Adinda Fairuz; Sibero, Hendra Tarigan; Graharti, Risti; Carolia, Novita (CV. Jasa Sukses Abadi, 2024)
Atopic dermatitis is a frequently occurring skin inflammation characterized by pruritus and lesions in specific areas such as the face and extremities. The majority of cases manifest during the first year of life, with a high prevalence among children under five years of age. In Europe, 118 million cases were recorded in 2023, whereas in Indonesia, the prevalence reached 10-20% among children and 1-3% among adults. This condition involves an interplay of exogenous and endogenous factors, including environmental exposure, genetic predisposition, immunological mechanisms, and colonization by Staphylococcus aureus. Environmental factors contributing to the incidence of atopic dermatitis include exposure to pollutants such as carbon monoxide, nitrogen dioxide, PM2.5, PM10, and volatile organic compounds (formaldehyde). Such exposure is a significant risk factor for atopic dermatitis in urban areas. This study aimed to analyze the correlation between residential areas and the incidence of atopic dermatitis at RSUD Dr. H. Abdul Moeloek during the period of January 2022 to July 2024. Data were collected from medical records, encompassing a total sample size of 82 patients. The chi-square test revealed a statistically significant relationship between residential area and the occurrence of atopic dermatitis, with individuals residing in urban areas being 0.23 times more likely to develop atopic dermatitis compared to those living in non-urban areas (p=0.02; OR=0.23)